2011
DOI: 10.1111/j.1743-6109.2011.02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Orgasm Is More Prevalent Among Women with a Prominent Tubercle of the Upper Lip

Abstract: Introduction Recent studies have uncovered multiple markers of vaginal orgasm history (unblocked pelvic movement during walking, less use of immature psychological defense mechanisms, greater urethrovaginal space). Other markers (perhaps of prenatal origin) even without obvious mechanistic roles in vaginal orgasm might exist, and a clinical observation led to the novel hypothesis that a prominent tubercle of the upper lip is such a marker. Aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…These results are consistent with the brain imaging differences noted by Komisaruk et al. , as well as clinical differences between vaginal orgasm and clitoral orgasm . Our finding that sexual arousability during stimulation of the shallow vagina was associated with sexual arousability during stimulation of the three other genital sites is consistent with the findings of Komisaruk et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with the brain imaging differences noted by Komisaruk et al. , as well as clinical differences between vaginal orgasm and clitoral orgasm . Our finding that sexual arousability during stimulation of the shallow vagina was associated with sexual arousability during stimulation of the three other genital sites is consistent with the findings of Komisaruk et al.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also indicate that deep vaginal sexual arousability is associated with sexual arousability at the other vaginal sites, but not the clitoris (implying differential activation). These results are consistent with the brain imaging differences noted by Komisaruk et al [2], as well as clinical differences between vaginal orgasm and clitoral orgasm [4,8,9,17,19,33]. Our finding that sexual arousability during stimulation of the shallow vagina was associated with sexual arousability during stimulation of the three other genital sites is consistent with the findings of Komisaruk et al [2] but also not inconsistent with the finding of Buisson et al [30,31] because of the correlation we observed between shallow vaginal and clitoral arousability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There appear to be both prenatal/perinatal and educational/developmental/experiential effects on likelihood of VO. An example of the former is the observation that women with a more prominent tubercle of the upper lip (which might be related to some aspects of fetal forebrain development) have a greater lifetime likelihood of VO (but not of CO) than women with flatter or concave tubercle areas [47]. An example of the educational aspect is the finding in a large representative sample that women who were educated in their youth that the vagina is a source of female orgasm (as opposed to either receiving no sex education, or being told that the clitoris is the sole source of female orgasm) have greater VO consistency [45].…”
mentioning
confidence: 99%
“…Some researchers use the terms “vaginally activated orgasm (VAO) as the climax obtained during vaginal penetration, without direct stimulation of the external clitoris” or “vaginal orgasm (VO)” (Jannini et al, ); “A woman's history of vaginal orgasm is discernible from her walk” (Nicholas et al, ); “Vaginal orgasm is more prevalent among women with a prominent tubercle of the upper lip” (Brody and Costa, ).…”
Section: Vaginal Orgasm Does Not Existmentioning
confidence: 99%